2017
DOI: 10.2152/jmi.64.136
|View full text |Cite
|
Sign up to set email alerts
|

Active stretching for lower extremity muscle tightness in pediatric patients with lumbar spondylolysis

Abstract: : Background : It was reported that hamstring muscle tightness may increase mechanical loading on the lumbar spine. Therefore, we attempt to decrease tightness in the leg muscles in pediatric patients. Methods : Forty-six pediatric patients with spondylolysis underwent rehabilitation. We applied active stretching to the hamstrings, quadriceps, and triceps surae. Tightness in each muscle was graded as good, fair, or poor. We educated each patient on how to perform active stretching at home. They were re-evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…Recently, Sato et al speculated that tightness of muscles in the region of the mobility joints, particularly the hip and ankle, may be the underlying pathology in pediatric patients with LS, and reported that active stretching with reciprocal inhibition was very effective for improving the flexibility of these joints (9). In the present study, we found that HBD was the item least likely to be…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Recently, Sato et al speculated that tightness of muscles in the region of the mobility joints, particularly the hip and ankle, may be the underlying pathology in pediatric patients with LS, and reported that active stretching with reciprocal inhibition was very effective for improving the flexibility of these joints (9). In the present study, we found that HBD was the item least likely to be…”
Section: Discussionsupporting
confidence: 56%
“…Many patients with LS are known to have tight hamstrings, quadriceps, and thoracic muscles (9), which may lead to compensatory movements and increased load at the lumbar spine. The aims of this study were to evaluate the physical features of pediatric patients with LS, to identify factors that increase their compensatory extension and/or rotation movements and loading at the lumbar spine, and to assess the effectiveness of rehabilitation in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…De acuerdo con la evidencia actual, un programa de flexibilidad podría ser efectivo para aumenta la extensibilidad muscular y el ROM de los movimientos clasificados con ROM limitado y mejorar el equilibrio muscular en la articulación (Iwata et al, 2019;Law et al, 2009;Sato et al, 2017). El diseño de un programa de flexibilidad eficaz debe seguir las siguientes recomendaciones: ≥2-3 días de frecuencia semanal, al menos una serie, entre 2 y 4 repeticiones, una intensidad de sensación de molestia muscular, técnicas de estiramiento variadas en función de la parte de la sesión de entrenamiento o el tipo de objetivo (estático -activo o pasivo, dinámico, balístico o facilitación neuromuscular propioceptiva) (Garber et al, 2011).…”
Section: Aplicaciones Prácticasunclassified
“…Compared to the method used in the present study, Sato [31] reported that an analysis of the changes in hamstring muscle tone and stiffness is a simple and effective way to evaluate stretching for hamstring flexibility. Neumann [32] suggested that increases in muscle length during stretching affect the force-length relationship.…”
Section: Discussionmentioning
confidence: 99%